Framtidens stadsträd för en fungerande grönstruktur - Johnander, Veronica (SLU/Dept. of Urban and Rural Development, 2010)
The effect of climate change places demands on how we build cities. Cities have to be built denser to meet the objectives of sustainability but as a result of this densification city green areas are at risk of exploitation and disappearing. The question this raises is whether there has to be an opposition between a dense and a green city?